Clinical conditions and echocardiographic parameters associated with mortality in COVID‐19. (20th July 2021) - Silverio, Angelo; Di Maio, Marco; Scudiero, Fernando; Russo, Vincenzo; Esposito, Luca; Attena, Emilio; Pezzullo, Salvatore; Parodi, Guido; D'Andrea, Antonello; Damato, Antonio; Silvestro, Antonio; Iannece, Patrizia; et al.
Abstract: Background: Coronavirus disease 2019 (COVID‐19) is a recently recognized viral infective disease which can be complicated by acute respiratory stress syndrome (ARDS) and cardiovascular complications including severe arrhythmias, acute coronary syndromes, myocarditis and pulmonary embolism. The aim of the present study was to identify the clinical conditions and echocardiographic parameters associated with in‐hospital mortality in COVID‐19. Methods: This is a multicentre retrospective observational study including seven Italian centres. Patients hospitalized with COVID‐19 from 1 March to 22 April 2020 were included into study population. The association between baseline variables and risk of in‐hospital mortality was assessed through multivariable logistic regression and competing risk analyses. Results: Out of 1401 patients admitted at the participating centres with confirmed diagnosis of COVID‐19, 226 (16.1%) underwent transthoracic echocardiography (TTE) and were included in the present analysis. In‐hospital death occurred in 68 patients (30.1%). At multivariable analysis, left ventricular ejection fraction (LVEF, P < .001), tricuspid annular plane systolic excursion (TAPSE, P < .001) and ARDS ( P < .001) were independently associated with in‐hospital mortality. At competing risk analysis, we found a significantly higher risk of mortality in patients with ARDS vs those without ARDS (HR: 7.66; CI: 3.95‐14.8), in patients with TAPSE ≤17 mm vs those with TAPSE >17 mm (HR: 5.08; CI: 3.15‐8.19) and in patients with LVEF ≤50% vs those with LVEF >50% (HR: 4.06; CI: 2.50‐6.59). Conclusions: TTE might be a useful tool in risk stratification of patients with COVID‐19. In particular, reduced LVEF and reduced TAPSE may help to identify patients at higher risk of death during hospitalization.